From Online Cart to Chart : Analytics Maturity Model for Retail E-Commerce SMEs - Tsutskov, Konstantin (2025)
In this master’s thesis, a design‑oriented, qualitative approach is employed to develop a data analytics maturity model for small and medium‑sized online retailers. The theoretical section delivers a focused synthesis of peer‑reviewed sources, exposing cost, sector, and scale‑related assumptions that are not relevant for SMEs, indicating gaps in currently developed analytics maturity models. Building on that analysis, the study proposes the Retail‑E‑Commerce Analytics Maturity Model (RECAMM), which arranges five core dimensions—Data, Tools, Skills, Culture, Strategy—across five evolutionary stages. The practical section applies a case‑informed design: six expert interviews, drawn from diverse retail verticals, validate and refine proposed model. The study thus links resource‑based and diffusion‑of‑innovation theory with everyday SME constraints, showing that non‑linear, resource‑sensitive analytics paths are both observable and workable. The developed model provides a roadmap for SMEs, industry practitioners to foster analytics-driven decision-making to foster business growth. Future research could expand its application to other sectors, undertake quantitative validation, and explore regional variations.